Linguistic loans in the current quechua of the communities of the Paccarectambo district - Palomino Gonzales, Niel (2019)
The research exposes and analyzes the main loanwords that native Quechua speakers from Paccarectambo district in Paruro province, Cuzco used during the first months of 2016 in their daily interaction. For this study, the conversations of the Quechua speaking farmers have been recorded in their different communicative situations like working the farm, resting, grazing cattle or traveling. Once the recording was finished, we proceeded with the transcription of audios. The age of Quechua-speaking farmers ranges about 50 to more years. With the transcribed texts, we built the CORQUERUPA abbreviation, (Paccarectambo Rural Quechua Corpus). This corpus was subjected to an analysis, mainly under the semantic, phonological and morphological lexical criteria. At the end, the results obtained show that in rural communities of Paccarectambo the Quechua language is full of loanwords mostly direct or indirectly from Spanish. One result also shows that the greatest number of loanwords belong to noun grammatical category. In addition, most of the loanwords have no equivalent in Quechua. On the other hand, the loanwords come from Latin that are adopted by the Quechua have undergone a morpho phonological adaptation that is the foreign words have adapted to the phonological and morphological Quechua system. Currently foreign words in Quechua are indirect and belong more to the noun category. Finally, the loan mechanism is proposed as a possibility to revitalize Quechua and make it a modern language with terms that can express diverse scientific concepts with precision and according to the characteristics of scientific language.